Risk of newly detected infections and cervical abnormalities in adult women seropositive or seronegative for naturally acquired HPV‐16/18 antibodies. (5th July 2019) - Rosillon, Dominique; Baril, Laurence; Del Rosario‐Raymundo, Maria Rowena; Wheeler, Cosette Marie; Skinner, Susan Rachel; Garland, Suzanne Marie; Salmeron, Jorge; Lazcano‐Ponce, Eduardo; Vallejos, Carlos Santiago; Stoney, Tanya; ter Harmsel, Bram; Lim, Timothy Yong Kuei; et al.
Abstract: Background: Infections with human papillomavirus (HPV) types 16 and 18 account for 70% of invasive cervical cancers but the degree of protection from naturally acquired anti‐HPV antibodies is uncertain. We examined the risk of HPV infections as defined by HPV DNA detection and cervical abnormalities among women >25 years in the Human Papilloma VIrus Vaccine Immunogenicity ANd Efficacy trial's (VIVIANE, NCT00294047) control arm. Methods: Serum anti‐HPV‐16/18 antibodies were determined at baseline and every 12 months in baseline DNA‐negative women (N = 2687 for HPV‐16 and 2705 for HPV‐18) by enzyme‐linked immunosorbent assay (ELISA) from blood samples. HPV infections were identified by polymerase chain reaction (PCR) every 6‐months, and cervical abnormalities were confirmed by cytology every 12 months. Data were collected over a 7‐year period. The association between the risk of type‐specific infection and cervical abnormalities and serostatus was assessed using Cox proportional hazard models. Results: Risk of newly detected HPV‐16‐associated 6‐month persistent infections (PI) (hazard ratio [HR] = 0.56 [95%CI:0.32; 0.99]) and atypical squamous cells of undetermined significance (ASC‐US+) (HR = 0.28 [0.12; 0.67]) were significantly lower in baseline seropositive vs baseline seronegative women. HPV‐16‐associated incident infections (HR = 0.81 [0.56; 1.16]) and 12‐month PI (HR = 0.53 [0.24; 1.16]) showed the same trend. A similar trend of lower risk was observed in HPV‐18‐seropositive vs ‐seronegative women (HR = 0.95 [0.59; 1.51] for IIs, HR = 0.43 [0.16; 1.13] for 6‐month PIs, HR = 0.31 [0.07; 1.36] for 12‐month PIs, and HR = 0.61 [0.23; 1.61] for ASC‐US+). Conclusions: Naturally acquired anti‐HPV‐16 antibodies were associated with a decreased risk of subsequent infection and cervical abnormalities in women >25 years. This possible protection was lower than that previously reported in 15‐ to 25‐year‐old women. Abstract : The degree of protection from naturally acquired HPV infection is uncertain. We analyzed 7‐year natural history data of women aged 25 or higher of the control cohort of a large, multinational, double‐blind, randomized, controlled trial. We observed that naturally acquired protection against HPV‐16 and, to a lesser extent, HPV‐18 was associated with lower risk of subsequent infection and cervical abnormalities in women >25 years.